Epigenome-wide DNA methylation profiling in comparison between pathological and physiological hypertrophy of human cardiomyocytes - Shi, Hangchuan; Chen, Si; Meng, Fanju W.; Ossip, Deborah J.; Yan, Chen; Li, Dongmei (Frontiers in Genetics, 2023)
Physiological and pathological stimuli result in distinct anatomic forms of cardiac hypertrophy, but the head-to-head comparison of molecular regulation between physiological and pathological cardiac hypertrophy is less well understood, especially at the DNA methylation level. We conducted an in vitro study using human cardiomyocytes exposed to angiotensin II (AngII) and insulin-like growth factor 1 (IGF-1) to mimic pathologically and physiologically hypertrophic heart models, respectively. Whole genome DNA methylation patterns were profiled by the Infinium human MethylationEPIC platform with >850K DNA methylation loci. Two external datasets were used for comparisons and qRT-PCR was performed for examining expression of associated genes of those identified DNA methylation loci. We detected 194 loci that are significantly differentially methylated after AngII treatment (vs control) with 50.0% hypermethylated, and 206 significant loci after IGF-1 treatment (vs control) with 45.1% hypermethylated (Adjusted P < 0.05). Mapping the significant loci to genes, we identified 158 genes corresponding to AngII treatment and 175 genes to IGF-1 treatment, with 67 genes overlapping between AngII and IGF-1. Using the gene-set enrichment analysis, the PI3K-Akt signaling pathway was identified to be significantly enriched for both AngII and IGF-1 treatment. The Hippo signaling pathway was enriched after IGF-1 treatment, but not for AngII treatment. Of the overlapped genes, CDK6 and RPTOR are components of the PI3K-Akt pathway but have different DNA methylation patterns in response to AngII and IGF-1. qRT-PCR confirmed the different gene expressions of CDK6 and PRTOR in response to both AngII and IGF-1 treatment on cardiomyocytes.